HUBUNGAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PUBLIK PADA PEMERINTAH KABUPATEN BENGKULU UTARA - Wijaya, Mirta; Susanti, Neri; Afriani, Sulisti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
irta Wijaya, Neri Susanti dan Sulisti Afriani; The purpose of this study is to determine the relationship between the accessibility of financial statements to public accountability to the Local Government of North Bengkulu Regency. Sampling method by purposive sampling. Analysis method using Spearman Rank Correlation analysis. From the research result, it can be concluded that there is a significant correlation between accessibility of financial report and public accountability to North Bengkulu Regency Government which seen from rs count> rs table (0,63> 0,450). While the strength of the relationship between the accessibility of the financial statements with public accountability is strongly apparent from the correlation value of 0.63 is at the interval of 0.60 - 0.799 with strong interpretation.Key Words: Financial reports, accessibility of financial statements, public accountability